Analytic Evaluation of a Human ELISA Kit for Measurement of Inhibin B in Rat Samples. (24th January 2013) - Coulson, Michelle; Bickerton, Sue; Betts, Catherine J; Jacobsen, Matt; Stewart, Jane; Chapin, Robert E.; Reagan, William J.; Alvey, James; Erdos, Zoltan; Saldutti, Louise Parks; Sonee, Manisha; Bogdan, Nancy; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND A cross‐laboratory analytic evaluation of a commercially available human inhibin B ELISA for measuring inhibin B in rat serum and plasma has been undertaken. METHODS Dilution linearity, spiked recovery, intra‐ and inter‐assay precision, functional sensitivity, matrix effects, and frozen stability were assessed across five laboratories. Reference ranges were generated for male Sprague Dawley and Han Wistar rats. RESULTS Acceptable performance was defined as an overall assay coefficient of variation ≤ 20% with an intraday LLOQ ≤ 20 pg/ml. Intra‐ and inter‐assay precision and functional sensitivity (≤6.4 pg/ml) generally met these criteria, but with occasional evidence of greater variability, particularly at lower concentrations. Dilution linearity was acceptable with occasional low recovery. Acceptable recovery of kit calibrators from rat serum confirmed the absence of matrix effects. Matched serum and plasma samples gave comparable results. The signal increased on freezing, remained constant for ≥3 freeze‐thaw cycles and was generally stable for at least 8 weeks. Mean inhibin B ranged from 33.5 to 140.6 pg/ml in adult rats across laboratories, with some evidence for a decline from 6 to 9 weeks of age. Power calculations using preliminary reference range data indicated 10 animals/group would generally detect a 40% decrease in inhibin B at AstraZeneca, but laboratories with lower control values would require larger groups. CONCLUSIONS The assay meets the analytical performance criteria; however, precision at the low end of the standard curve, biological variability, and low control values observed in some laboratories indicate that the utility of the assay may be limited in some laboratories.